The Diference Level Of Anxiety In Pre Surgery Sectio Caesarea Before And After Classical Music Treatmentin Teratai Room of Kediri Regency Hospital. - yunarsih -; nurma p (JURNAL KEBIDANAN, 2016)
Sectio Caesarea surgery can make a patient experiencing anxiety. Granting of classical music therapy is an independent nursing actions to cope with anxiety. Where in fact classical musics have a balance between the four elements of music that is melody, harmony, rhythm and timbre. It has a relaxing effect sinaffected brain wavesso the patient's body become relaxed and have an impact on decreasing the stress response can beused to intervenein the anxietyof the patient pre-registration operations sectio caesarea. This research using pre experimental design with the approach of one group pre post test.Sampling using consecutive sampling with the total sampleas much of the eight respondents. The Taylor Manifest Anxiety Scale (T-MAS)are used as a measure of anxiety. Data analysis statistical test used was a non parametric Wilcoxon. From there sultstatistic using Wilcoxon Match Pair Tests howing p value 0,011than(p<0,05) there are difference in patient sanxiety level pre operation sectio caesarea before and after the a warding of the classical music therapy in Kediri Regency Hospital. The showing that giving of the influence classical music classic in lowering anxiety scor eso can help the patient intension or anxiety. Isuggest that health worker more care dpsychologis patient pre-operation sectio caesarea and influence factors.